Information Spotlighting in Americans' Decisions Surrounding Refugee Resettlement Policy. (3rd September 2019) - Garinther, Alexander; Mayorga, Marcus; Västfjäll, Daniel; Slovic, Paul
Abstract: Violent conflict in the Middle East has forced millions to flee their homes and seek refuge in host nations around the globe. Across three studies, we asked American participants ( N ∼ 1, 500) to consider a refugee-resettlement policy that would bring displaced families from the Middle East into their communities, and tracked the items of information these Americans were interested in seeing during the consideration of their decision. Results suggest that participants who rejected the resettlement policy were especially concerned with security-related information and uninterested in humanitarian-related information, while participants who supported the policy expressed interest in a more balanced ratio of security and humanitarian-related information. We situate these findings within the broader literature on attitude-confirming behaviour (e.g. conformation bias, selective exposure) and discuss how information spotlighting might exacerbate polarization on politically charged issues like refugee policy.